1979
DOI: 10.1128/iai.26.2.573-579.1979
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immunity in the resolution of genital infection in female guinea pigs infected with the agent of guinea pig inclusion conjunctivitis

Abstract: Female guinea pigs infected in the genital tract with the chlamydial agent of guinea pig inclusion conjunctivitis were selectively immunosuppressed by varying regimens of cyclophosphamide (Cy) treatment. Temporary suppression of both humoral and cell-mediated immunity by daily treatment of Cy (25 mg/kg) for 13 days resulted in a prolonged infection, whereas daily treatment for the duration of the experiment totally prevented the development of humoral and cell-mediated responses and produced an intense and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 16 publications
2
59
0
Order By: Relevance
“…However, in laboratory animals other than the mouse there has been controversy for a number of years over the relative role of antibody or cell mediated immunity in protection. Few of these experiments could be regarded as definitive from a modern perspective, but it appears that in the guinea pig specific antibodies may play a more prominent role in protection compared to the mouse [23,[26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…However, in laboratory animals other than the mouse there has been controversy for a number of years over the relative role of antibody or cell mediated immunity in protection. Few of these experiments could be regarded as definitive from a modern perspective, but it appears that in the guinea pig specific antibodies may play a more prominent role in protection compared to the mouse [23,[26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, previous studies have indicated that secretory immunoglobulin A (IgA) and IgG have protective roles during genital chlamydial infection (1-4, 21, 38). However, recent studies using experimental animal models of genital chlamydial disease have clearly established that T-cell-mediated immunity (CMI), usually involving gamma interferon (IFN-␥), is crucial for chlamydial control (5,8,13,14,16,18,29,30,33,34,36,37,41,44,45,49,52). Additional studies revealed that the resistance of experimental animals to genital reinfection by Chlamydia was associated with the pres-ence of relatively high intensity of antigen-specific T lymphocytes in the genital tract tissue (15).…”
Section: Genital Infection By the Obligate Intracellular Bacteriummentioning
confidence: 99%
“…In the female genital tract, the shedding of the infected cells from the cervical epithelium results in their migration down the genital tract to the vagina. This was actually observed over and over when we collected secretions and cells from the vagina and quantified the percentage of cells infected with GPIC ( Barron et al, 1979;Rank et al, 1979). We routinely observed apparently healthy cells with inclusions at all stages of the developmental cycle as well as large numbers of PMNs.…”
Section: Discussionmentioning
confidence: 80%